PERUBAHAN SOSIAL EKONOMI MASYARAKAT DI KELURAHAN GUNUNG SARIK KECAMATAN KURANJI KOTA PADANG - Palmasri, Palmasri; Bakaruddin, Bakaruddin; Zuriyani, Elvi (Pendidikan Geografi, 2013)
This study aims to determine the socio-economic changes of community  in Sarik Mount Village district of Kuranji Padang city  that includes : 1 ) Livelihood, 2 ) Education and 3 ) land area residents.This research is descriptive. The population in this study were all residents in Sarik Mount Village district of Kuranji Padang  city  totaling 3,701 households. Samples were taken in 2 ways, with engineering samples taken territory taken by porposive sampling technique (designation) is just taking RW I, RW III , VIII and RW  RW  X,  his  appointment  basis  for  4  to  the  region  which  is  a  region experiencing  housing  development  56  the  number  of  households,  while  the sample region taken with total sampling at 56 KK .The research found that: 1) There were changes  in the livelihoods of the changes  in  peoples  livelihoods,  livelihood  development  after  the  livelihood  of farmers were 21 respondents ( 37,5 % ), while 24 respondents ( 42,9 % ) switched to merchant and (19,6 % ) and changes to labor income levels before and after the development of housing  in Sarik Mount Village district of Kuran ji Padang  city  in one  month,  (2)  There  were  changes  in  family  education,  especially  school dropouts decreased ( from 33.9 % to 7,1 % ) and the cause of children dropping out  of  school  before  and  after  the  land  turned  into  housing  is  the  cost  factor (33,9%  to  5,4% ) and ( 3 ) There is a change in the amount of agricultural land area of 24 hectares, before the development of the average farmers had 1,5 ha and 2 ha ( 33,9%), while after the development of the community who do not have the existing  agricultural  land  (26,8%).  Before  the  agriculture  land  residential development  generally  rice  (100,0%)  and  after  the  development  of  paddy  stay (73.2 % ). Landowners who turns are as many as 19 people with an area of 24 ha